Companies' perspectives on factors affecting consumer satisfaction in fast-food restaurant using Fuzzy AHP / Suzanawati Abu Hasan ... [ et al.] - Abu Hasan, Suzanawati; Hassan, Nur Aqilah; Teoh, Yeong Kin; Mahat, Norpah; Ariffin, Anas Fathul (Universiti Teknologi MARA, Perlis, 2021)
In today's world, the fast-food restaurant has become a popular sort of eatery. The fast-food industry's expansion is always changing in response to customer requests in order to meet their needs. As a result, clients have a wide range of fast-food restaurants to choose from in order to satiate their hunger. Clients' contentment with restaurants will influence not just the image of the establishments, but also the services offered by their employees as they strive to entertain and deliver the best possible service to their paying customers. However, the competition between the restaurants have caused certain restaurants to gain lower profits as the customers' satisfaction is not fulfilled for certain factors. Price, food quality, service quality, restaurant atmosphere, promotion, customer expectations, and brand are all elements to consider. This study was conducted to analyse the importance of factors in customer satisfaction in a fast-food restaurant in Perlis. In this study, the method applied is the Fuzzy Analytical Hierarchy Process (AHP) to rank the factors that have a high impact on customer satisfaction. The selected fast-food restaurants were McDonald (McD), Kentucky Fried Chicken (KFC), Pizza Hut, Domino's Pizza, Marrybrown, and Subway. The primary data collected through the questionnaire were analysed by experts, the manager of the fast-food restaurant selected. The findings show that in a fast-food restaurant, the quality of service with 0.2188 of normalized weight is the most important factor in customer satisfaction, and the price with 0.0436 of normalized weight is the least significant. The role of the manager and the staffs were thus evidently more important in customer satisfaction than the price offered.